Green Synthesis of Silver Nanoparticles via Cratoxylum glaucum Leaf Extract Loaded Polyvinyl Alcohol and Its Antibacterial Acitvity - Verry Andre Fabiani; Rahmad Lingga (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
In this study, green synthesis of silver nanoparticles via Cratoxylum glaucum leaf extracts loaded with polyvinyl alcohol and its bacterial activity were tested. Nanosilver from ‘Pucuk Idat’ leaves has a non-uniform size and tends to agglomerate, making the nanoparticle size unstable and challenging to apply further. Therefore, so that nanoparticles do not aggregate, efforts are made to add stabilizers. Polyvinyl alcohol (PVA) is a polymer that can be used as a stabilizer because it can prevent unwanted aggregation and oxidation processes. UV-Vis analysis results show that PVA as a stabilizer can avoid an increase in wavelength shift. Based on the results of this XRD analysis, it can be concluded that in this research sample, the silver nanoparticle is formed with a cubic crystal system, and it can be observed that the smallest average particle size is in the 0.75% Ag/PVA sample of 10.32 nm. Furthermore, based on the antibacterial test against E. coli and S. aureus, it can be explained that the 0.75% PVA-modified nanosilver sample showed weak to medium antibacterial activity..